2019
DOI: 10.1016/j.amj.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Management of Sleepiness Among Pilots in a Norwegian and an Austrian Air Ambulance Service—A Comparative Study

Abstract: We compared subjectively reported sleepiness and fatigue as well as causes and management strategies for combating sleepiness among pilots working in 2 different helicopter emergency medical services operating with different shift systems. Methods: Pilots from the Norwegian Air Ambulance (NAA) and Christophorus Flugrettungsverein (CFV) in Austria participated. NAA performs flight missions 24/7, whereas at the time of the study the participating CFV bases did not fly after sunset. The pilots are on duty for 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The average nocturnal sleep duration for Norwegian men is 6:52 h (Ursin et al 2005), suggesting that adequate amounts of sleep seemed to have been obtained. A previous study comparing Norwegian and Austrian HEMS pilots found that 24% of the Austrian and 71% of Norwegian pilots report using sleep as a mitigating measure against sleepiness, suggesting on-duty Norwegian pilots are better at using sleep facilities when needed (Zakariassen et al 2019). Additionally, 78% of the workers in the present study had children living at home and 40% kept a second job during their weeks off work.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The average nocturnal sleep duration for Norwegian men is 6:52 h (Ursin et al 2005), suggesting that adequate amounts of sleep seemed to have been obtained. A previous study comparing Norwegian and Austrian HEMS pilots found that 24% of the Austrian and 71% of Norwegian pilots report using sleep as a mitigating measure against sleepiness, suggesting on-duty Norwegian pilots are better at using sleep facilities when needed (Zakariassen et al 2019). Additionally, 78% of the workers in the present study had children living at home and 40% kept a second job during their weeks off work.…”
Section: Discussionsupporting
confidence: 45%
“…The organization of HEMS varies considerably between countries regarding both work schedules and settings. The work schedules of different HEMS in Europe vary greatly -from 12, 24, and 48 h shifts in Netherland and Finland (Radstaak et al 2014;Sallinen et al 2018), and up to 7 consecutive 24 h shifts in Norway and Austria (Zakariassen et al 2019). Some live on the helicopter base, while others commute every day, and there are also differences regarding the extent to which the crew takes on missions after dark (Radstaak et al 2014;Zakariassen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The crew can also have to decline missions if they have exceeded the duty hours. After working 14 h of the last 24 h, they are obliged to rest the next 8 h. These HEMS regulations help maintain flight safety [ 31 ]. As a consequence of the increased use of the HEMS, more missions could be declined despite of being medically warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of these types of training was shown to reduce self-reported fatigue and to improve sleep quantity and performance ( Rosekind et al, 2006 ; van Drongelen et al, 2014 ). Inadequate sleep hygiene and environmental factors preventing sleep are still reported and remain areas for improvement ( Zakariassen et al, 2019 ). In addition, getting optimal amounts of good quality sleep is especially difficult for persons on military deployment ( Kelly and Efthymiou, 2019 ).…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…Daytime naps, before shift work decrease fatigue and increase performance, as do naps during the night shift ( Garbarino et al, 2004 ; Brooks and Lack, 2006 ; Caldwell et al, 2009 ; Ruggiero and Redeker, 2014 ; Martin-Gill et al, 2018 ). Both daytime and night-time naps are commonly used in military and commercial aviation ( Petrie et al, 2004 ; Gregory et al, 2010 ; Kelly and Efthymiou, 2019 ; Zakariassen et al, 2019 ). Pilots aged >50yrs.…”
Section: Preventive Strategiesmentioning
confidence: 99%